2007
DOI: 10.1002/mop.22517
|View full text |Cite
|
Sign up to set email alerts
|

A novel design of a microstrip‐fed shorted square‐ring slot antenna for circular polarization

Abstract: The design of a circularly polarized slot antenna fed by a single microstrip line is presented. The circularly polarized radiation is achieved by means of using a shorted square‐ring slot. This proposed antenna has the fundamental resonant frequency of 2.4 GHz with the minimum return loss of −50.44 dB. The impedance bandwidth is 930 MHz or 38.7% referred to the resonant frequency, and it also has the 3‐dB axial‐ratio (AR) bandwidth of 310 MHz or 12.9% referred to the resonant frequency. In addition, this propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…The optimized value of the L 16 is given in Section 2. It can be observed that increasing the length of L 16 , causes a decrease on the center frequencies of all three impedance bands. But the change of the first band is more noticeable.…”
Section: Studying Effects Of L 16mentioning
confidence: 93%
See 2 more Smart Citations
“…The optimized value of the L 16 is given in Section 2. It can be observed that increasing the length of L 16 , causes a decrease on the center frequencies of all three impedance bands. But the change of the first band is more noticeable.…”
Section: Studying Effects Of L 16mentioning
confidence: 93%
“…The impedance matching bandwidths of the first and third bands become much smaller when the length of L 16 increases, while the second band becomes much wider. On the other hand increasing the length of L 16 , creates the CP at the first band, between 2.38 ∼ 2.78 GHz, but through Figure 6, it could be understood that the CP bandwidth does not guarantee the impedance matching bandwidth for the same frequency band.…”
Section: Studying Effects Of L 16mentioning
confidence: 99%
See 1 more Smart Citation
“…References [5][6][7] realized the UHF RFID antenna but its size is too large to facilitate the practical application. References [8,9] developed a small circularly polarized RFID antenna, but the antenna bandwidth is so narrow that it cannot meet the requirements of UHF RFID applications. In this letter, a new compact CP and low cost design of a square-ring microstrip antenna with a vertical slotted ground plane are proposed.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], an intricate UWB antenna with a CP band of 7.18-10.01 GHz was introduced. Presence of a ring type slot in antenna structure generates circularly polarized waves [6], whereas, shorted square-ring slot can create CP [7]. A circularly polarized square slot antenna loaded with a cross patch is published in [8].…”
mentioning
confidence: 99%